2020
DOI: 10.1038/s41598-020-61883-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Alzheimer’s Disease Loci Using Sex-Specific Family-Based Association Analysis of Whole-Genome Sequence Data

Abstract: With the advent of whole genome-sequencing (WGS) studies, family-based designs enable sex-specific analysis approaches that can be applied to only affected individuals; tests using family-based designs are attractive because they are completely robust against the effects of population substructure. These advantages make family-based association tests (FBATs) that use siblings as well as parents especially suited for the analysis of late-onset diseases such as Alzheimer's Disease (AD). However, the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…We have demonstrated that folate-deficient mice which exhibit cognitive impairment also have an increase in Tomm40 expression further implicating this gene. Grid1 expression in human females is positively correlated with protection from AD risk (63). Our study with cognitively impaired female mice demonstrated a downregulation of Grid1 (2.9-fold down, P < 0.001; Supplementary Table 3) which also suggests the positive correlation of Grid1 expression and cognitive health.…”
Section: Discussionsupporting
confidence: 62%
“…We have demonstrated that folate-deficient mice which exhibit cognitive impairment also have an increase in Tomm40 expression further implicating this gene. Grid1 expression in human females is positively correlated with protection from AD risk (63). Our study with cognitively impaired female mice demonstrated a downregulation of Grid1 (2.9-fold down, P < 0.001; Supplementary Table 3) which also suggests the positive correlation of Grid1 expression and cognitive health.…”
Section: Discussionsupporting
confidence: 62%
“…As the use of polygenic risk scores (Box 1) is proving beneficial for predicting disease risk (Box 4), the same approach may be applied to sex-specific risk. Furthermore, family-based analytical designs, which robustly recapitulate population structure, can be employed to test for sex-specific disease risk loci (Prokopenko et al, 2020). In addition to the sex-dependent effect described for APOE, other genetic and genomic factors contribute to LOAD in a sex-specific manner, as we review here.…”
Section: Sex-by-gene Interactions In Loadmentioning
confidence: 99%
“…rs13115400 Female-specific association with LOAD and Aβ42 levels (Deming et al, 2018) MCPH1 rs13259125 Increased risk in males; protection in females (Prokopenko et al, 2020) MPO rs2333227 Increased risk in females, reduced risk in males (Reynolds et al, 1999) NGFR rs2072446 Increased risk in females (Matyi et al, 2017) RELN rs528528 Increased risk in males (Fehér et al, 2015) rs607755…”
Section: Linc00290mentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to low statistical power to robustly detect sex-specific loci in AD after sample stratification, few studies have investigated sex difference effects through a classical GWAS approach to identify variants associated with the AD diagnosis in case-control cohorts (Nazarian et al, 2019). Other study paradigms such as incorporating familybased association design or leveraging neuropathological features as AD endophenotypes have found sex-specific associations (Deming et al, 2018;Dumitrescu et al, 2019;Prokopenko et al, 2020). In addition to detecting sex-specific loci, some studies identified significant sex-specific predictors for AD phenotypes such as neuropathology (Deming et al, 2018), biomarkers (Dumitrescu et al, 2019), and age at onset using polygenic hazard scores (Fan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%